Targeted metabolomics reveals serum changes of amino acids in mild to moderate ischemic stroke and stroke mimics - Tao, Shuxin; Xiao, Xinxing; Li, Xin; Na, Fan; Na, Guo; Wang, Shuang; Zhang, Pin; Hao, Fang; Zhao, Peiran; Guo, Dong; Liu, Xuewu; Yang, Dawei (Frontiers in Neurology, 2023)
Background: The pathophysiological processes linked to an acute ischemic stroke (IS) can be reflected in the circulating metabolome. Amino acids (AAs) have been demonstrated to be one of the most significant metabolites that can undergo significant alteration after a stroke. Methods: We sought to identify the potential biomarkers for the early detection of IS using an extensive targeted technique for reliable quantification of 27 different AAs based on ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). A cohort with 216 participants was enrolled, including 70 mild to moderate ischemic stroke patients (National Institutes of Health Stroke Scale＜15, MB group), 76 stroke mimics (MM group) and 70 healthy controls (NC group). Results: It was found that upon comparing MB and MM to control patients, AAs shifts were detected via partial least squares discrimination analysis (PLS-DA) and pathway analysis. Interestingly, MB and MM exhibited similar AAs pattern. Moreover, ornithine, asparagine, valine, citrulline, and cysteine were identified for inclusion in a biomarker panel for early-stage stroke detection based upon an AUC of 0.968 (95% CI 0.924–0.998). Levels of ornithine were positively associated with infract volume, 3 months mRS score, and National Institutes of Health Stroke Scale (NIHSS) score in MB. In addition, a metabolites biomarker panel, including ornithine, taurine, phenylalanine, citrulline, cysteine, yielded an AUC of 0.99 (95% CI 0.966–1) which can be employed to effectively discriminate MM patients from control.